Electroluminescent Guest@MOF Nanoparticles for Thin Film Optoelectronics and Solid‐State Lighting. Issue 16 (11th June 2020) - Gutiérrez, Mario; Martín, Cristina; Van der Auweraer, Mark; Hofkens, Johan; Tan, Jin‐Chong
Abstract: Light‐emitting diodes (LEDs) are an efficient source of lighting, with many commercial applications like general illumination, camera flashes, phone or laptop displays, and TV screens. However, they present certain limitations, including low‐quality color rendition, and the use of expensive/toxic rare‐earth elements. There is therefore an urgent need for the development of improved luminescent materials free of rare earths. Luminescent metal–organic framework (LMOF) materials are promising candidates for photonics devices. Most MOF‐LEDs reported are of the down‐converter type, where UV or blue LED are coated with LMOFs, however there is limited progress in the development of LED using LMOFs as the electroluminescent layer. Herein, it is reported a novel Guest@MOF composite synthesized by encapsulating a semiconducting Gaq3 metal complex [gallium(III) tris(8‐hydroxyquinolinato)], into the ZIF‐8 pore [Zn (2‐methylimidazolate)2 ], yielding a green‐yellowish luminescent material exhibiting a relatively high quantum yield of 15% upon photoexcitation. Subsequently, a down‐converter LED comprising 405‐nm violet LED coated with Gaq3@ZIF‐8, yielding a white MOF‐LED is shown. Then the use of Gaq3@ZIF‐8 as an electroluminescent layer in a hybrid‐LED, achieving an orange‐yellowish light emitting device is demonstrated. This work reveals the potential of LMOFs for next‐generation LED technology, by exploiting the Guest@MOF concept to enable electroluminescent applications. Abstract : Rapid nanoscale confinement of a semiconducting Gaq3 metal complex within ZIF‐8 yields a new luminescent dye@MOF composite system. The resulting material termed Gaq3@ZIF‐8 exhibits excellent photophysical properties, with robust long‐term stability thanks to guest–host shielding. Electroluminescent MOF‐LED device is constructed and tested with a low turn‐on voltage of 3 V.